A Comprehensive Review on Load Frequency Control in Renewable-Integrated and HVDC-Connected Power Systems (International Journal of Engineering & Extended Technologies Research (IJEETR), 2026)
The rapid integration of renewable energy sources and the widespread adoption of high voltage direct current (HVDC) transmission links have significantly altered the operational dynamics of modern interconnected power systems, leading to reduced system inertia, increased uncertainty, and greater frequency instability. Under such conditions, Load Frequency Control (LFC) plays a vital role in maintaining system reliability by regulating frequency deviations and tie-line power exchanges in multi-area networks. This review provides a comprehensive overview of LFC strategies in renewable-integrated and HVDC-connected power systems, covering the impact of wind, solar, energy storage systems, and electric vehicles on frequency dynamics and system stability. It critically examines conventional and advanced control approaches, including PI/PID, fractional-order, model predictive, adaptive, and intelligent optimization-based controllers such as fuzzy logic, machine learning, and nature-inspired algorithms, in the context of hybrid AC/DC grids. The role of HVDC technologies, including LCC and VSC systems, in providing virtual inertia, fast frequency support, and enhanced power sharing is also discussed. In addition, emerging challenges such as cyber-attacks, low-inertia operation, communication delays, and coordinated control with energy storage devices are analysed to highlight their influence on LFC performance. A comparative synthesis of recent studies is presented based on key performance indicators such as settling time, overshoot, robustness, and disturbance rejection, followed by the identification of research gaps and future directions toward developing resilient, AI-driven, and cyber-secure frequency control frameworks for next-generation renewable-dominated power systems.
Keywords: Load Frequency Control; Renewable Energy Integration; HVDC-Connected Power Systems; Frequency Stability; Intelligent Control Techniques; Low-Inertia Power Systems